Banking Regulation and Financial Accelerators: A One-Period Model with Unlimited Liability - Wolfgang Bühler; Christian Koziol (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
In this paper, we analyze the consequences of bank regulation on the size of the real sector. In particular, we address the question whether exogenous shocks on the return-risk characteristics of the technology and on the equity of the real sector are intensified or damped by a value-at-risk constraint on the credit portfolio of a bank. We consider a one-period model with three risk-averse agents, an investor, a bank, and a firm. The size of the markets for deposits and loans, their prices and the size of the real sector are endogenous. We find that stricter regulation results in higher loan rates, lower deposit rates, and lower activity in the real sector. A negative shock on the return-risk position or on the risk buffer of the real sector reduces the activities in the economy. Surprisingly, the sensitivity of the real sector's activities on negative shocks is smaller for a regulated financial sector than for a non-regulated one. Therefore, in our economy, imperfections in the financial sector do not result in procyclical or acceleration effects.
urn:nbn:de:bvb:19-epub-13531-8
Keywords: 330